Moodle and Facebook as virtual learning teaching tools of mediation: the opinion of teachers and university students - Delgado-García, Manuel; García-Prieto, Francisco Javier; Gómez Hurtado, Inmaculada (Revista Complutense de Educación, 2017)
Introduction of tools as virtual platforms or social network to the university means a new construction of learning-teaching process. This research analyzes the educational and didactic utility of Moodle platform and Facebook to identify its potentialities and controversies. It is presented a descriptive and interpretative study which combines qualitative and quantitative design, in order to know the opinion of the professors and students in degrees in the Faculty of Educational Sciences of the University of Huelva (Spain). The results stress the importance of the previous training, the positive assessment of its didactic use, the increase of the collaboration due to its accessibility. In conclusion, the information we collected shows the relevance of using these tools in student learning and as the need for a change in both as much educational structures and teaching training in order to improve the quality of the teaching.